Preincubation of donor tissue with a VEGF cytokine trap promotes subsequent high-risk corneal transplant survival. Issue 11 (22nd November 2021) - Zhang, Wei; Schönberg, Alfrun; Hamdorf, Matthias; Georgiev, Tihomir; Cursiefen, Claus; Bock, Felix
Abstract : Aims: Pathological neovascularisation of the host bed and the transplant itself is the main risk factor for graft rejection after corneal transplantation. This study aims to prevent this process by preincubation of the corneal donor tissue ex vivo with an antivascular endothelial growth factor (VEGF) cytokine trap blocking additional postsurgical hemangiogenesis and lymphangiogenesis to promote high-risk graft survival. Methods: The donor tissue was preincubated with a VEGFR1R2 cytokine trap for 24 hours prior to murine high-risk corneal transplantation (human IgG Fc was used as the control). The distribution of VEGFR1R2 Trap in the cornea was investigated by immunohistochemistry. Corneas were excised to quantify the blood vessels (BVs) and lymphatic vessels (LVs) and draining lymph nodes (dLNs) were harvested to analyse the phenotype of dendritic cells (DCs) and T cells at week 1, 2 and 8 post-transplantation. Graft survival was compared between preincubation with VEGFR1R2 Trap and human IgG Fc in high-risk recipients. Results: VEGFR1R2 Trap was present in the graft for at least 2 weeks after surgery and additionally diffused into the corneal recipient. BVs, LVs and macrophages in the whole cornea were significantly decreased 1-week and 2-week post-transplantation (p<0.05). In dLNs the frequency of CD11c+DCs was significantly reduced, whereas CD200R+ regulatory DCs were significantly increased after keratoplasty (p<0.05). Furthermore, long-term high-risk graft survival was significantly improved (p<0.01). Conclusions: Preincubation of corneal donor tissue with a VEGFR1R2 cytokine trap can significantly promote subsequent high-risk corneal transplant survival and thereby opens new treatment avenues for high-risk corneal transplantation.